Job Satisfaction and Retention Strategies for Generation-Y: Evidence from Thailand - Anuphanpisit, Rinrat (2016)
According to the high turnover rate of Generation-Y in current Thai labour market, it is crucial for companies to notice their Generation-Y employees’ job satisfaction in order to create efficient retention strategies. This research reveals many factors that affect job satisfaction in Thai Generation-Y employees from different companies and industries. From the result, there are eleven factors are mentioned by Thai Generation-Y employees that they affect their job satisfaction in the current job. A Good relationship with co-workers and managers factor is the first factor that is referred by all Thai Generation-Y employees from any industries. Following by the second which is Values of work, then Pay and Benefits is the Third factor. The fourth are Brand of the company, Feedbacks from managers or customers, Good Training and Development, Good career path. The fifth is Work-life balance and the sixth are Flexibility, Freedom and Empowerment, and Generation gap. It seems that Thai Generation-Y employees place important on the Intrinsic factors more than Extrinsic (Hygiene) factors. Some factors of job satisfactions in current Thai Generation-Y employees is distinct from Western Generation-Y employees, but not too much. Thai Generation-Y employees are more concentrate on Brand of the company, Good career paths and Generation gap, but the previous scholars from the Western did not highly mention about these factors. In contrast, the Western Generation-Y saw Technologies in workplace and Organisation policies (CSR) as crucial factors, but Thai Generation-Y does not refer these factors in this research.